Neuroinflammation and brain–peripheral interaction in ischemic stroke: A narrative review - Cheng, Wenjing; Zhao, Qing; Li, Chengzhen; Xu, Yunzhi (Frontiers in Immunology, 2023)
Excessive immune activation within the lesion site can be observed after stroke onset. Such neuroinflammation within the brain parenchyma is the innate immune response, as well as the result of additional interactions between peripheral and resident immune cells. Accumulative studies have illustrated that the pathological process of ischemic stroke is associated with resident and peripheral immunity. The infiltration of peripheral immune cells within the brain parenchyma implicitly contributes to the secondary brain injuries. Therefore, better understanding of the role of resident and peripheral immune reactions toward ischemic insults is necessary. In this review, we summarized the interaction between peripheral and resident immunity on the systemic immunity and clinical outcome after stroke onset, and also discussed various potential immunotherapeutic strategies.